Nadiem Makarim’s Speech: A Critical Discourse Analysis at National Education Day - Achmad Ivansyah Obos; Bibit Suhatmady; Yuni Utami Asih (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Background: National Education Day, the most important day for education in Indonesia, serves as the chief podium for the minister of education. Analyzing Nadiem Makarim’s speech through the viewpoint of Fairclough, who offers a three-dimensional framework for text and discourse, was the focus of critical discourse analysis. Methodology: This study uses a descriptive qualitative method by conducting a Critical Discourse Analysis approach. The data for this research is a transcript of Nadiem Makarim's speech at the time of National Education Day 2022 and analyzed through data reduction, data display, and drawing the conclusion. Findings: At the micro-level, Nadiem Makarim’s speech employed diction to emphasize the position of the people who would be participating in his speech. The lexical structures used are polysemy, metonymy, synonym, collocation, and a contrasting conjunction. At mezzo-level, the text was a transcript that was published on May 12, 2022, on the websites. At macro-level, the speech was given during the National Education Day ceremony, demonstrates the situational level. The institutional level proved during his tenure gave the speech. The social level demonstrates that both the audiences' and all Indonesians' reactions to Minister’s speech were positive and negative. Conclusion: With his speech, Nadiem Anwar Makarim received special attention from the community because of his role as an important person. The information he conveyed has made the researchers find the macro, mezzo, and micro levels. It is important to know the meaning of the speech so the listeners may have a different perspective in give their opinion. Originality: This research uses the newest National Education Day 2022 speech by Nadiem Makarim and the Critical Discourse Analysis approach to get the micro, mezzo and macro levels.